Sistema autônomo de bombeamento de água acionado por painéis fotovoltaicos amorfo e policristalino - Zilli, Bruno Meneghel (2018)
Water resources have fundamental importance both for life of living beings and for human activities. The lack of water can be a limiting factor for occupation and development of a certain region. Pumping systems are an alternative solution for these cases, with electric generation from photovoltaic panels being a locally pollutant-free option with less maintance when compared to combustion-generation engines. This work aims the analysis of a photovoltaic pumping system with two cell technologies, amorphous silicon and polycrystaline. The experiment was installed in the dependencies of the State University of West Paraná – campus Cascavel-PR. The data of voltage and electric current generated by panels, ambient and panels temperature, solar irradiation and water flow were collected. From these data, the volume pumped in the establised period, the flow as a function of the irradiation and the energy consumed, the behavior of the available and consumed energies, as well as the panel’s temperature on efficiency, were analyzed. The average volume pumped was 2,255.44 and 2,397.01 liters per day in the amorphous and polycrystalline systems, respectively. The best efficiency results in both systems were given at 800 W m-2, 4,69% for amorphous and 7,75% polycrystaline. However, the firt one presented lower voltage drop with panel’s temperature increasing. It was obtained higher flow and overall efficiency in the polycrystalline system.